First large‑scale study reveals important losses of managed honey bee and stingless bee colonies in Latin America - Requier, Fabrice; Sibaja Leyton, Malena; Morales, Carolina L.; Garibaldi, Lucas Alejandro; Giacobino, Agostina; Porrini, Martin Pablo; Rosso‑Londoño, Juan Manuel; Velarde, Rodrigo A.; Aldea‑Sánchez, Patricia; Allasino, Mariana Laura; Bulacio Cagnolo, Natalia Veronica; Landi, Lucas; et al. (Springer Nature, 2024)
Over the last quarter century, increasing honey bee colony losses motivated standardized large-scale surveys of managed honey bees (Apis mellifera), particularly in Europe and the United States. Here we present the first large-scale standardized survey of colony losses of managed honey bees and stingless bees across Latin America. Overall, 1736 beekeepers and 165 meliponiculturists participated in the 2-year survey (2016–2017 and 2017–2018). On average, 30.4% of honey bee colonies and 39.6% of stingless bee colonies were lost per year across the region. Summer losses were higher than winter losses in stingless bees (30.9% and 22.2%, respectively) but not in honey bees (18.8% and 20.6%, respectively). Colony loss increased with operation size during the summer in both honey bees and stingless bees and decreased with operation size during the winter in stingless bees. Furthermore, losses differed significantly between countries and across years for both beekeepers and meliponiculturists. Overall, winter losses of honey bee colonies in Latin America (20.6%) position this region between Europe (12.5%) and the United States (40.4%). These results highlight the magnitude of bee colony losses occurring in the region and suggest difficulties in maintaining overall colony health and economic survival for beekeepers and meliponiculturists.